FENOMENA DAN KONSTRUKSI KOMUNIKASI MASYARAKAT DI SEKITAR TWA SORONG PAPUA BARAT - Mutiono (Jurnal Komunikasi Pembangunan, 2020)
Management of conservation areas cannot be separated from the existence of the surrounding communities. One important aspect in understanding society is to know the construction of communication that develops in a community group. This study aims to uncover the phenomenon of communication that develops in the communities around TWA Sorong along with its construction as an implication of community interaction with the surrounding forest resources. This research is based on a constructivist paradigm with a qualitative approach. The strategy used is a case study strategy through observation, interviews and desk study methods. The results showed a symbolic convergence phenomenon that caused asymmetric information between the government and the community in the historical context of TWA Sorong and could lead to legal but not legitimate conditions. Symbolic convergence is strongly constructed by oral tradition communication and characteristics of village communities that are still strong with adat and customary rights.